Behavior theory and human models - BANDURA, A. (Psichologija, 1997)
The translated speech of A. Bandura in which he presents the major moments of his theory (modelling, reinforcement, self-reinforcement, self-regulation). The theory is compared with behaviorist theory. The philosophical approach to human is also presented.